Assessing the risk caused by ground level ozone to European forest trees: a case study in pine, beech and oak across different climate regions. - Emberson, Lisa D.; Büker, Patrick; Ashmore, Mike R. (Environmental pollution (Barking, Essex : 1987), 2007)
Two different indices have been proposed for estimation of the risk caused to forest trees across Europe by ground-level ozone, (i) the concentration based AOT40 index (Accumulated Over a Threshold of 40 ppb) and (ii) the recently developed flux based AFstY index (Accumulated stomatal Flux above a flux threshold Y). This paper compares the AOT40 and AFstY indices for three forest trees species at different locations in Europe. The AFstY index is estimated using the DO(3)SE (Deposition of Ozone and Stomatal Exchange) model parameterized for Scots pine (Pinus sylvestris), beech (Fagus sylvatica) and holm oak (Quercus ilex). The results show a large difference in the perceived O(3) risk when using AOT40 and AFstY indices both between species and regions. The AOT40 index shows a strong north-south gradient across Europe, whereas there is little difference between regions in the modelled values of AFstY. There are significant differences in modelled AFstY between species, which are predominantly determined by differences in the timing and length of the growing season, the periods during which soil moisture deficit limits stomatal conductance, and adaptation to soil moisture stress. This emphasizes the importance of defining species-specific flux response variables to obtain a more accurate quantification of O(3) risk.
The following values have no corresponding Zotero field: accession-num: 17412465
Keywords: Beech (Fagus sylvatica); Critical levels; Deposition; Flux; Forests; Holm oak (Quercus ilex); Ozone; Scots pine (Pinus sylvestris); stomata